Post-Pandemic Analysis of Governance and Performance in Indonesia’s Regional Development Banks - ., Taufiqurrahman; Alwie, Alvi Furwanti (Journal of Ecohumanism, 2024)
This study examines the governance structures and mechanisms influencing the performance of Indonesia’s regional development banks (BPDs) during and beyond the COVID-19 pandemic. By analyzing financial and annual reports from 27 regional development banks across Indonesia, the study explores both the immediate and lasting impacts of governance elements, including board size, board independence, and committee structures, on bank performance. Using a two-stage least squares (2SLS) regression model, findings reveal that certain governance elements, such as the risk monitoring committee size, positively impacted performance during the pandemic, whereas larger board sizes and higher board independence were associated with negative outcomes. Additionally, other governance factors, such as board meeting frequency and audit committee size, did not significantly influence performance during the crisis. The research highlights that the stability observed in BPDs during the pandemic was primarily driven by external factors, including regional economic growth and credit expansion, rather than governance mechanisms alone. These findings suggest that while crisis-era governance structures were adequate during the pandemic, post-pandemic recovery and resilience will require more adaptable governance frameworks. As BPDs face evolving challenges in the financial sector, this study underscores the importance of enhancing strategic oversight and adjusting governance practices to foster long-term stability. This research contributes to the literature on governance and crisis management in regional banks, offering insights for regulators and practitioners seeking to reinforce governance frameworks that support sustainable performance in the face of new economic realities.